Rapid and accurate identification and differentiation of Mycobacterium tuberculosis and non-tuberculous mycobacteria using PCR kits available in a high-burden setting - Bernardo Castro-Rodriguez; Greta Franco-Sotomayor; Greta Franco-Sotomayor; Ángel Sebastián Rodriguez-Pazmiño; Greta Esther Cardenas-Franco; Solón Alberto Orlando; Solón Alberto Orlando; Javier Hermoso de Mendoza; Henry Parra-Vera; Miguel Ángel García-Bereguiain (Frontiers Media S.A., 2024)
Infections caused by mycobacteria, including Mycobacterium tuberculosis complex (MTBC) and non-tuberculous mycobacteria (NTM), are a major public health issue worldwide. An accurate diagnosis of mycobacterial species is a challenge for surveillance and treatment, particularly in high-burden settings usually associated with low- and middle-income countries. In this study, we analyzed the clinical performance of two commercial PCR kits designed for the identification and differentiation of MTBC and NTM, available in a high-burden setting such as Ecuador. A total of 109 mycobacteria isolates were included in the study, 59 of which were previously characterized as M. tuberculosis and the other 59 as NTM. Both kits displayed great clinical performance for the identification of M. tuberculosis, with 100% sensitivity. On the other hand, for NTM, one of the kits displayed a good clinical performance with a sensitivity of 94.9% (CI 95%: 89-100%), while the second kit had a reduced sensitivity of 77.1% (CI 95%: 65-89%). In conclusion, one of the kits is a fast and reliable tool for the identification and discrimination of MTBC and NTM from clinical isolates.